Analysis, modeling, and simulation of emergency department - Natasha Stojkovik; Limonka Koceva Lazarova; Dimitrievska Ristovska, Vesna; Maja Kukuseva; Aleksandra Stojanova Ilievska (Scientific Technical Union of Mechanical Engineering" Industry 4.0", 2022)
Overcrowding in the Emergency Department (ED) is one of the most important issues in healthcare systems. Two major causes of this congestion are identified, the first one is unjustified Emergency Department visits and the second one a lack of downstream beds. The lack of downstream beds can deteriorate the quality of care for patients who need hospitalization after an ED visit. In this paper a generic simulation model is developed in order to analyse patient pathways from the ED to hospital discharge.
Keywords: EMERGENCY DEPARTMENT, GENERIC SIMULATION MODEL, AGENT BASED MODELING, ANYLOGIC